SPEECH ACT THEORY - Mo‘minova , Xulkaroy; Gulbahor, Roziqova (Educational Research in Universal Sciences, 2023)
This research gives a general overview to Speech Acts with relevant examples. The kinds of speech acts; locutionary acts, illocutionary acts, representative, directive, commissive, expressive and declarative.